To study the various parameters for bioconversion of glucose to gluconic acid by Penicillium chrysogenum in submerged culture - Swapnil D. Topre2, Sreejit S. Panikar2, Dinesh S. Labade3, Nilesh K. Purane1*, Shital K. Sharma1 (Recent Research in Science and Technology, 2011)
The present study was focused on optimization of various submerged fermentation parameters as glucose concentration, inoculum density and inoculum age for gluconic Acid (GA) production by P. chrysogenum 724. At 100 gL-1 glucose concentration, the maximum value of GA concentration (31.16 gL-1) with high productivity (0.33 gL-1h-1) was achieved over 96 hours. On other hand, lower productivity (0.24 gL-1h-1 & 0.21 gL-1h-1) was obtained at higher glucose concentration level (150 gL-1 & 200 24 & 48 hours gL-1) respectively. The level of GA production was higher at 10% inoculum density as compared to 5% & 20%, also showed a constant increase of GA production (31.36 gL-1) with high production rate (0.33 gL-1h-1) and selectivity (79.66 %) over 96 hours. The inoculum age with 72 hours was showed stable GA production (31.36 gL-1) with higher productivity (0.33 gL-1h-1) in comparison other inoculum age (24 & 48 hours).